Study of Optimization of Plastic Waste Pyrolysis into Gasoline Fuel - Yulistianto, Arief; Ruhama, Ade; Romadona, Iqbal; Ichsan, M. Ibrahim; Robiansyah, Muhammad; Prawoto; Maulana, Eka (Magister Teknik Mesin Universitas Pancasila, 2025)
Pyrolysis, which converts plastic waste into energy through a heating process without oxygen, has been proven to reduce waste volume by up to 90% while becoming an alternative fuel with high economic value. The optimal pyrolysis temperature of 380°C produces the most significant amount of pyrolysis oil, with a potential thermal efficiency of up to 80%. The main challenges in optimizing pyrolysis include energy efficiency, operational costs, and production scale. This study aims to improve the efficiency of the pyrolysis process by enhancing the reactor, condenser tube, and control system. With this approach, it is hoped that a more cost-effective, environmentally friendly plastic waste management solution can be created that supports the concept of a circular economy in Cirebon City. The result is that with a plastic waste composition of 30% PP and 70% LDPE and the addition of a kaolin catalyst to the pyrolysis reactor, it can produce oil equivalent to gasoline with an octane rating of 88. This optimization can reduce the use of fossil fuels, create new jobs, and significantly contribute to environmental sustainability.